Characterizing the Impact of Selective Laser Melting on Complex Lattice Geometries using Finite Element Analysis - Santanna, Euclides; Anflor, Carla (Revista Interdisciplinar de Pesquisa em Engenharia, 2023)
Additive manufacturing (AM) has made significant strides in industries over the past century. Manufacturing techniques employing metallic dies have found applications across various engineering fields, particularly where there is a need for components that are both lightweight and durable. In the pursuit of optimizing both shape and performance, researchers have delved into the examination of lattice structures, often referred to as fill geometries. Among these geometries, certain examples exhibit intriguing properties such as a negative Poisson’s ratio, as seen in auxetic structures, or an optimized mass/volume ratio, exemplified by the Gyroid structure. The primary aim of this endeavor is to delve into the analysis and characterization of metallic additive manufacturing through the employment of the Selective Laser Melting (SLM) technique. The focus extends to comprehending how this technique impacts intricate geometries, particularly those involving lattice structures. The methodology involves leveraging computer simulations using the ANSYS® software to execute studies utilizing finite element analysis. These studies serve the purpose of thoroughly delineating the effects of the additive manufacturing process in AM.